Catalyst-free reactions under biocompatible conditions - Ren, Mi (2023)
Catalyst-free biocompatible reactions are a class of green chemical processes that are also applicable to the field of chemical biology. In this account, we detail our journey in this exciting area of research since 2000. Various types of catalyst-free biocompatible reactions, such as the Mukaiyama aldol reactions and thiol-specific click reactions, and their applications to the functionalization of proteins are described. These reactions work well without destroying the three-dimensional structures of the proteins. Other reactions, including the C- SO2 and C-N bond-forming reactions, are also discussed. These reactions work in a truly green manner in which the use of organic solvents can be totally avoided. This toolbox of green chemical processes will certainly facilitate the work of researchers in the pharmaceutical industries.